Social Media Marketing and Customer Review’s Influence towards Visit Decisions at Gunung Kidul Beach Tourists Attraction (Universitas Terbuka, 2023)
This study aims to explore the relationship between social media marketing, customer review, and visit decisions in the context of Gunung Kidul beach tourists attractions. This research explores the phenomenon of tourists who keep on coming to visit Gunung Kidul beach even though there are minimal infrastructure facilities. Library study method was selected for this study because it is suitable for analyzing existing body of knowledge and identifying patterns, trends, and gaps in the literature. This approach involves reviewing and synthesizing articles, books, journals, conference proceedings and other credible sources, related to the impact of social media marketing and customer reviews on visiting decisions. The number of sources used in this research is around 20. The findings of this study reveal interesting insights about the dynamics of social media marketing and customer review in the context of Gunung Kidul beach tourism object. This research shows that social media marketing and customer review have a positive impact on the formation of trust among tourists. From the analysis that has been carried out, social media marketing and customer reviews have a positive relationship with the decision to visit. This study combines two variables that are not combined much, social media marketing and customer review to determine the influence on the decision to visit. This research contributes to a comprehensive understanding of the interactions betweensocial media marketing, customer review and visit decisions, offering practical insights for promoting sustainable tourism development in Gunung Kidul, Yogyakarta.